Fluorescent diagnosis and photodynamic therapy for C6 glioma in combination with antiangiogenic therapy in subcutaneous and intracranial tumor models - Tzerkovsky, D.A.; Osharin, V.V.; Istomin, Y.P.; Alexandrova, E.N.; Vozmitel, M.A. (Experimental Oncology, 2014)
Objective: Investigating the distinctions pharmacokinetics of chlorin e6 conjugated with polyvinyl pyrrolidone photosensitizer (Ce6CPPPS)in healthy and tumor tissues of rat brain and evaluating the antitumor efficacy of combination treatment for C6 rat glioma including photodynamic (PDT) and antiangiogenic therapy (AAT). Materials and Methods: The study was performed on 50 white random-bred rats in subcutaneous and intracranial models of C6 glioma. Photosensitizer (PS) Ce6CPPPS single injection at a dose of 2.5 mg/kg was made into the animal’s caudal vein. The PS accumulation level in brain tissues and C6 rat glioma was measured with spectral fluorescence technique using LESA-01-Biospek spectrum analyser (Russian Federation, Moscow; λ = 632.8 nm). Photoirradiation of intracranial and subcutaneous C6 glioma was carried out with a light exposure dose of 50 J/cm2 (IMAF-Axicon, Republic of Belarus; λ = 661 nm). AAT drug bevacizumab, single injection was made intravenously at a dose of 10 mg/kg 24 h after tumor photoirradiation. The criteria for efficacy evaluation were mean survival time (MST) and median survival of the animals in the study group vs the control and the percentage of tumor necrosis areas induced by the above-mentioned treatment. Results: The optimal time for photoirradiation of intracranial C6 glioma is 0.5 h after Ce6CPPPS injection. The combination therapy group demonstrated a statistically significant MST increase (38.4 ± 4.39 days) compared with the PDT group (29.2 ± 3.5 days) (p = 0.02) and the AAT group (27.1 ± 2.74 days) (p = 0.02). Necrosis areas in tumor tissue were as follows: the intact control — 10.0 ± 2.55%, PDT — 54.87 ± 6.95% (p = 0.003), AAT — 57.83 ± 6.53% (p = 0.003) and combination therapy — 89.43 ± 5.57% (p = 0.001). Conclusions: This paper is the first report about feasibility of efficient use of PDT with a PS of chlorin series and AAT with bevacizumab for the treatment of brain tumors in experimental models. Key Words: Ce6CPPPS, bevacizumab, glioma C6, photodynamic therapy, antiangiogenic therapy.